Performance Evaluation of Penstock By-Pass System Modification on HEPP (Hydro Electric Power Plant) with CFD Analysis to Optimize Power Consumption. Issue 1 (June 2021) - Harpendi; Sugianto; Wijanarko, Dwi; Caesarendra, Wahyu
Abstract: This paper proposes a feasibility test for the performance modification of the penstock by-pass system using CFD (Computational-Fluid-Dynamic) simulations to optimize the energy use of the water-cooling system. The main advantage of this modification is the power savings of 45%-50%. This modification of the by-pass system is carried out with the aim that the final flowrate and pressure of modification can replace the Main-Water-Supply-Pump (MWSP) operation function in the unit's main cooling system. CFD simulation is carried out on the impact of a pressure drop of 40-4 bar with a flow of 0.3 m3/s on the by-pass pipe flow of the existing penstock system and the condition of the pipe modification to be carried out. The numerical simulation results show that the MWSP network structure can accept load flow pressures varying 40-4 bar. This simulation refers to the conditions in HEPP Saguling Indonesia and can be applied to others.